2008
DOI: 10.1016/j.cell.2008.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Cell Shape and Negative Links in Regulatory Motifs Together Control Spatial Information Flow in Signaling Networks

Abstract: The role of cell size and shape in controlling local intracellular signaling reactions, and how this spatial information originates and is propagated, is not well understood. We have used partial differential equations to model the flow of spatial information from the beta-adrenergic receptor to MAPK1,2 through the cAMP/PKA/B-Raf/MAPK1,2 network in neurons using real geometries. The numerical simulations indicated that cell shape controls the dynamics of local biochemical activity of signal-modulated negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
299
2
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 280 publications
(332 citation statements)
references
References 46 publications
19
299
2
6
Order By: Relevance
“…The ERK-PDE4 motif could signal in other receptor systems that induce the simultaneous activation of PKA and ERK, such as the beta-adrenergic receptor in the hippocampus (28,31). This motif could also be a potential point of integration for Gs-coupled receptors and ERK activating agents such as growth factors, chemokines, and cytokines in many tissues and cell types.…”
Section: Discussionmentioning
confidence: 99%
“…The ERK-PDE4 motif could signal in other receptor systems that induce the simultaneous activation of PKA and ERK, such as the beta-adrenergic receptor in the hippocampus (28,31). This motif could also be a potential point of integration for Gs-coupled receptors and ERK activating agents such as growth factors, chemokines, and cytokines in many tissues and cell types.…”
Section: Discussionmentioning
confidence: 99%
“…Development of a spatiotemporal model that accounts for diffusive transport along the dendrite with shape change of the spine is an important direction in our future work. Spatial compartmentalization of signaling and shape can affect the dynamics of the activity of different signaling molecules in cell motility (30,(62)(63)(64). Membrane mechanics studies have shown that protein interaction with the membrane cannot only induce a curvature but also, change membrane properties (65).…”
Section: Discussionmentioning
confidence: 99%
“…Dynamical modeling using ordinary differential equations approaches has been used to test hypotheses in silico, generate time courses, and identify emergent properties that would be hard to investigate experimentally. This approach has been used in neuroscience successfully to study different aspects of structural plasticity (21,29,30). In this study, using computational models, we seek to answer the following questions.…”
Section: Significancementioning
confidence: 99%
“…The full MATLAB scripts are available upon request. As we have done in our previous work (39,75,76), most of the model parameters were obtained from the literature. Unknown parameters were constrained using published data, such as the cGMP-dependent activation of PDE2 (22), or data generated by us, such as the cAMP or surface GluA1 increases because of PDE2 inhibition (supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%